Early mortality after late initiation of antiretroviral therapy in the TREAT Asia HIV Observational Database (TAHOD) of the International Epidemiologic Databases to Evaluate AIDS (IeDEA) Asia‐Pacific. Issue 6 (18th December 2019) - Rupasinghe, D; Kiertiburanakul, S; Kamarulzaman, A; Zhang, F; Kumarasamy, N; Chaiwarith, R; Merati, TP; Do, CD; Khusuwan, S; Avihingsanon, A; Lee, MP; Ly, PS; et al.
Abstract : Objectives: Early mortality among those still initiating antiretroviral therapy (ART) with advanced stages of HIV infection in resource‐limited settings remains high despite recommendations for universal HIV treatment. We investigated risk factors associated with early mortality in people living with HIV (PLHIV) starting ART at low CD4 levels in the Asia‐Pacific. Methods: PLHIV enrolled in the Therapeutics, Research, Education and AIDS Training in Asia (TREAT Asia) HIV Observational Database (TAHOD) who initiated ART with a CD4 count < 100 cells/μL between 2003 and 2018 were included in the study. Early mortality was defined as death within 1 year of ART initiation. PLHIV in follow‐up for > 1 year were censored at 12 months. Competing risk regression was used to analyse risk factors with loss to follow‐up as a competing risk. Results: A total of 1813 PLHIV were included in the study, of whom 74% were male. With 73 (4%) deaths, the overall first‐year mortality rate was 4.27 per 100 person‐years (PY). Thirty‐eight deaths (52%) were AIDS‐related, 10 (14%) were immune reconstituted inflammatory syndrome (IRIS)‐related, 13 (18%) were non‐AIDS‐related and 12 (16%) had an unknown cause. Risk factors included having a body mass index (BMI) < 18.5 [sub‐hazard ratio (SHR) 2.91; 95% confidence interval (CI) 1.60–5.32] compared to BMI 18.5–24.9, and alanine aminotransferase (ALT) ≥ 5 times its upper limit of normal (ULN) (SHR 6.14; 95% CI 1.62–23.20) compared to ALT < 5 times its ULN. A higher CD4 count (51–100 cells/μL: SHR 0.28; 95% CI 0.14–0.55; and > 100 cells/μL: SHR 0.12; 95% CI 0.05–0.26) was associated with reduced hazard for mortality compared to CD4 count ≤ 25 cells/μL. Conclusions: Fifty‐two per cent of early deaths were AIDS‐related. Efforts to initiate ART at CD4 counts > 50 cell/μL are associated with improved short‐term survival rates, even in those with late stages of HIV disease.